PENGARUH FINANCIAL PRESSURE TERHADAP TAX AVOIDANCE DENGAN DISCLOSURE AND TRANSPARENCY SEBAGAI VARIABEL MODERATING - Puspita Handayani; Nurhayati Nurhayati (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
The research objective is to examine and analyze the effect of financial pressure on tax avoidance with disclosure and transparency as moderating variables in banking companies. The variables of this study consist of the dependent variable, namely tax avoidance as measured by Cash ETR and BTD, financial pressure as measured by ROA, CAR, DER, NPL and Size as independent variables and disclosure and transparency as moderating variables. This research was conducted on banking companies because the characteristics of the banking industry are different from other industries. This sector is very closely related to good corporate governance because of regulations. Disclosure and transparency variables are added as moderating variables because the banking industry is a trust-based industry, to increase investor confidence, banks need to increase transparency and accountability. The research method uses causality, the data used is secondary. The data collection procedure is carried out using the documentation method, data from the Indonesia Stock Exchange (www.idx.co.id). The population is banking companies listed on the Indonesia Stock Exchange in the period 2014-2020, the sampling technique uses purposive sampling and the number of research samples is 49 companies. Data analysis techniques and hypothesis testing with the help of PLS. The results show that financial pressure has a negative effect on tax avoidance and disclosure and transparency cannot moderate the relationship between financial pressure and tax avoidance.Keywords: Tax Avoidance; Financial Pressure; Disclosure and Transparency